The Combination of Benson Relaxation and Pelvic Tilting on the Scale of Low Back Pain in Pregnant Women - Rinda Harwidiana Rani; Harmayetty Harmayetty; Tiyas Kusumaningrum (Universitas Airlangga, 2020)
Introduction: Lower back pain in pregnant women trimester II and III causes difficulty in standing or even moving from bed, and the lousy impact is difficulty in walking if it has spread to the lumbar or pelvic region. The study aimed to know the effects of the combination of Benson relaxation and pelvic tilting on back pain in pregnant women.Methods: The research was Quasi-experiment. The population is second-trimester pregnant women who experience lower back pain in the Public Health Center Mojo and Public Health Center Gading, Surabaya. Purposive sampling was used to gain 56 respondents. The independent variable of this study was the second trimester pregnant women with low back pain treated for two weeks. The dependent variable was the intensity of the pain level. Research data obtained by pre-test and post-test with VAS questioner. Analyzed using the Wilcoxon sign rank test and Mann- Whitney test.Results: As a result of the combination of Benson's relaxation and pelvic tilting, there was an influence on the back pain of second-trimester pregnant women. Based on the Mann-Whitney test, there were significant differences in the treatment group or the control group with p = 0.000.Conclusion: The combination of Benson relaxation and pelvic tilting decreases the scale of low back pain in pregnant women. Pelvic tilting is more influential because it can reduce the pain scale.